Bureau of Boarding and Community Development (BPPM) and Actualization of Social Fiqh Kiai Sahal - Agil Muhammad (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2023)
This paper attempts to analyze the concept and actualization of Kiai Sahal’s social fiqh within the BPPM institution which is linked to his social movement through analysis of Max Weber’s theory of social action which aims to understand the motives and goals of the perpetrator, namely Kiai Sahal, in pioneering and developing BPPM. From the study conducted, it can be seen that Kiai Sahal sees the need for fiqh in overcoming the problems of community life as a form of maslahah al-ammah and the realization of sa’adah al-darain. Kiai Sahal’s movement in community empowerment through BPPM is included in the category of instrumental rationality social action, because this social movement begins through a process of calculation and consideration in the form of reading the social reality of the surrounding community and this action has the aim of strengthening social, economic, educational, and health aspects that support perfection of worship, which is the actualization of Kiai Sahal’s social fiqh thinking